The Impact of Digitalization on the Labor Market - Aslonov Jurabek Mansurovich (International Journal on Integrated Education, 2026)
This article presents a comprehensive analysis of the transformation of the labor market and labor relations in the context of digital technological development. It examines the growing demand for new skills and competencies in the digital economy, with particular emphasis on the role and significance of basic, transversal, and digital technical skills. The study also analyzes the contribution of digital platforms and innovative technologies to increasing employment, enhancing labor productivity, and creating new jobs. In addition, it explores the negative effects of robotization and automation on the labor market, including the decline of certain professions and the increased risk of unemployment.